Audio Visual sebagai Media Pemahaman Pulsa, Tempo dan Nilai Not dalam Pembelajaran Musik - Aryuda Fakhleri Fallen; Yudi Sukmayadi (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: This article aims to describe the idea of designing learning video products related to the material "Knowing Pulse, Tempo, and Note Values in Music" The aim being pursued is to bridge teachers in carrying out the process of learning arts and culture (music), the material being concentrated is related to the time element (rhythm). Rhythm, which contains pulses, tempos and note values, is seen as the essential foundation where the orientation will later be related to music learning, both from a scientific and practical point of view. So the urgency of the media that is carried out considers aspects that support the effectiveness of learning. Method: In this writing, the research model used is Research and Development (R&D) with the 4D approach, which Thiagarajan pioneered. Product development has been in the 2D (Design) stage. Where the media offered is based on research results or observations at the primary level in music learning, then media development is based on selecting the type of media to be developed. Considering the internet access that can be reached from anywhere and anytime, the authors chose learning videos as a product so that later they can be disseminated to teachers who will carry out rhythm-related learning. Result and Discussion: The learning video requires sound, image and movement components to be combined simultaneously to bridge the basic foundation in recognizing time elements in music; the speed chosen is at a tempo of 60 Bpm.